CBS News Monthly Poll #1, March 2008 ([Verlag nicht ermittelbar], 2009)
This poll, fielded March 15-18, 2008, is a part of a continuing series of monthly surveys that solicit public opinion on the presidency and on a range of other political and social issues. This poll included an oversample of African Americans, for a total of 122 African American respondents. Respondents were asked whether they approved of the way George W. Bush was handling the presidency, the economy, and the situation in Iraq, to rate the condition of the national economy, to indicate the most important issue for candidates to discuss in the 2008 presidential election, and the preferred qualities and characteristics in a presidential candidate. Registered voters were asked how much attention they were paying to the 2008 presidential campaign, whether they planned to or had already voted in a Democratic or Republican primary or caucus in their state, their opinions of candidates John McCain, Barack Obama, and Hillary Clinton, and which candidate they would vote for if the general election were held that day. Views were sought on the news media's treatment of the candidates, whether it was appropriate for candidates to show their emotions in public, whether respondents and most people they knew would vote for a presidential candidate who was African American or a woman, whether people they knew had made sexist or racist remarks in the past few months, and whether racism or sexism was a more serious problem in the country. Registered Democratic primary voters were asked about the Democratic presidential nomination process and how superdelegates should decide their vote at the convention. Additional questions queried all respondents on Obama's minister Reverend Jeremiah Wright, major league baseball, steriod use in professional sports, the war in Iraq and its effect on the threat of terrorism against the United States, and whether Saddam Hussein was personally involved in the terrorist attacks of September 11, 2001. Demographic variables include sex, age, race, education level, marital status, whether respondents had children under 18 years of age, household income, political party affiliation, political philosophy, voter registration status and participation history, religious preference, frequency of religious attendance, and whether respondents considered themselves to be a born-again Christian.